Experimental evaluation and analysis of 18650 battery energy capacity and performance parameters - Czerniak, Jacek; Gacek, Anna; Ziembik, Zbigniew (Scientific Papers of Silesian University of Technology. Organization and Management Series, 2025)
Purpose: The primary objective of this paper was to present the research findings on 18650 batteries, with an emphasis on consumer selection practices, as well as the challenges and support mechanisms related to product quality. Additionally, the study aimed to identify critical issues that could inform future legislative changes related to 18650 batteries. Design/methodology/approach: The study employed a survey-based methodology, wherein participants were queried regarding the battery features they prioritize during their procurement process. The second phase of the study involved technical measurements of selected 18650 batteries, including their actual capacity and mass. A measurement system was designed and implemented, utilizing a solution that optimally replicated the user's real-world battery charging conditions. Findings: The web-survey allowed for the identification of the most important characteristics of batteries from the customers' perspective. As a result of the research, significant discrepancies were found between the declared and measured parameters of the batteries. It was identified that there is a lack of legal regulations governing the quality parameters that are important to consumers of this type of energy source. Research limitations/implications: The necessity for establishing appropriate standards for 18650 batteries has been demonstrated. Practical implications: Considering the number of charge and discharge cycles for these products, batteries with lower capacities impose a substantial environmental and economic burden, as they require more frequent replacement and recycling. Social implications: The need to enhance production and quality control standards for 18650 batteries has been emphasized to ensure the production of high-quality products that minimize environmental impact while maximizing consumer benefits. Originality/value: The parameters of 18650 batteries most relevant to consumers are presented, along with discrepancies between the specifications declared by manufacturers and their actual performance. The findings can assist producers in making informed decisions during the prototyping phase to enhance product quality, and guide legislators in developing appropriate legal standards. Keywords: lithium-ion batteries, energy capacity, quality, customer. Category of the paper: Research paper.